AB163. Which the specific pathophysiologies is higher in simplified international index of erectile function (IIEF-5) among ED patients? - Tang, Yuxin (Transl Androl Urol, 2014)
OBJECTIVES: To compare the IIEF-5 score among ED patients with specific pathophysiologies. METHODS: We studied the IIEF-5 score of 3,327 ED patients (median age 39 years) whose primary pathophysiological causes were established by comprehensive diagnostic procedures in the urology/andrology clinics of five training hospitals in China. RESULTS: One hundred and seventy-six patients were excluded, other patients (n=3,151) with duration of ED between 0.5 year and 20 years were enrolled. The causes of ED was found be psychogenic (59.2%), vasculogenic (21.3%), neurogenic (4.1%), anatomical/structural (2.8%), hormonal (7.1%) or drug-induced (5.5%). A significant difference was detected in the median IIEF-5 score between the subjects with psychogenic and organic ED [15 (IQR: 13, 17) vs. 12 (IQR: 9.5, 14.5), P<0.001]. There was no significant difference among the organic groups (P=0.073), and no significant difference was found between arteriogenic and venogenic cause [13 (IQR: 10.5, 15.5) vs. 13 (IQR: 11, 15), P=0.912 (adjusted α =0.017)]. CONCLUSIONS: Although the IIEF-5 score of men with psychological ED is greater than those with organic causes, there is no difference among patients with different organic pathophysiologies. The IIEF-5 is suitable to be a screening tool; however, our data indicate that IIEF-5 is not a definitive diagnostic tool to discriminate the pathophysiological causes of ED.